Detection of alphaviruses in a genus-specific antigen capture enzyme immunoassay using monoclonal antibodies. - Greiser-Wilke, I M (1991)
A genus-specific antigen capture assay using similar combinations of monoclonal antibodies for capture and detection of 24 alphaviruses belonging to the seven serocomplexes was developed. The sensitivity of the test ranged from 10(3.4) 50% tissue culture infective doses/ml for o'nyong-nyong virus to 10(6.1) 50% tissue culture infective doses/ml for Middelburg virus. The antigen capture test uses a combination of cross-reacting monoclonal antibodies directed against the nucleocapsid protein and envelope glycoprotein E1 of Semliki Forest virus.